Anodized Steel: The Most Promising Bifunctional Electrocatalyst for Alkaline Water Electrolysis in Industry. (25th March 2022) - Zhou, Pengfei; Niu, Pengda; Liu, Jishan; Zhang, Nian; Bai, Haoyun; Chen, Mingpeng; Feng, Jinxian; Liu, Di; Wang, Litong; Chen, Shi; Kwok, Chi Tat; Tang, Yuxin; et al.
Abstract: Electrolysis of water, especially alkaline water electrolysis (AWE), is the most promising technology to produce hydrogen in industry. However, only 4% of the total hydrogen is produced in this way because the electrode materials are expensive, inefficient, or unstable. Here, it is reported that the large‐scale 3D printed martensitic steel (AerMet100) can be the bifunctional electrode for AWE with high catalytic performance, which may dramatically increase the green‐hydrogen percentage in the market and provide strategic planning for energy management. It is found that the martensitic steel by fast anodization (3 min) can realize ultra‐high hydrogen and oxygen evolution reactions (HER and OER), and excellent stability at high current densities. Particularly, this electrocatalyst shows a low overpotential of 3.18 V and long‐term stability over 140 h at 570 mA cm −2 in overall water splitting. Additionally, the treated large‐scale steel can work well under a very high current up to 20 A. This study demonstrates that martensitic steel can be commercialized as a highly efficient catalyst for industrial hydrogen production in AWE, which should provide solutions to the energy crisis and environmental pollution. Abstract : An AerMet100 martensite steel (Fe‐13.37Co‐11.37Ni‐3.21Cr‐1.24Mo‐0.22C)‐based electrocatalyst is prepared by fast anodization (3 min), which can realize ultra‐high HER and OER performances, and excellent long‐term stability at high current densities in overall water splitting. The AerMet100 martensitic steel has commercial prospects as a highly efficient catalyst for industrial hydrogen production in alkaline water electrolysis.